ANALISIS BENTUK-BENTUK LAPORAN KEUANGAN DAN EFEKTIVITAS LAPORAN KEUANGAN PADA UMKM (Studi Kasus pada UMKM kelompok Perajin Kuningan di Kecamatan Juwana Tahun 2011) - Rosadi, Samsul - (Universitas Slamet Riyadi, 2014)
ABSTRACT The purpose of this study were (1) To know the presentation forms of financial report on SMEs in the sub-group of Juwana’s craftsmen brass, (2) To know the effectiveness of the financial reports presentation on SME brass craftsmen groups in Juwana’s District. Technique of data analysis used is an interactive model of data analysis techniques. According to the result of study can be concluded that, (1) SME group of brass craftsmen in Juwana already presenting financial reports, but of the 10 SMEs only 4 SMEs that presents financial reports in accordance with GAAP while the other SMEs only make a business report which are not in accordance with GAAP. (2) The effectiveness of the financial reports are measured by the two parties, the intern and the extern have two working systems in the operations is as follows: (a) the internal parties are the owners of SMEs, nine owners of SMEs stated that the presentation of financial reports they made have been effective only 1 of SMEs stating that financial reports made less effective because the expenditure book larger than the book income, this was due to delay payment of accounts receivable, (b) an external party is extern party of SMEs such as banks and government, the outsider asses that external financial reporting is effective if made in accordance with GAAP. Keywords: forms of financial report, effectiveness of the financial reports, SMEs.